Effect of lanthanides on red blood cell deformability and response to mechanical stress: Role of lanthanide ionic radius - ÜYÜKLÜ, MEHMET; Alexy, Tamas; Baskurt, Oguz K.; NEMETH, Norbert; Uyuklu, MEHMET; Wenby, Rosalinda B.; Meiselman, Herbert J. (My University, 2011)
Prior studies exploring the effects of lanthanides (Ln) on red blood cells (RBC) have primarily focused on ion transport, cell fusion, and membrane protein structure. Our previous report [Biorheology 44 (2007), 361-373] dealt only with lanthanum (La) and cell rigidity; the present study extends these observations to other lanthanides (Nd, Sm, Eu, Dy, Er) and to RBC response to mechanical shear. Deformation-shear stress behavior of normal human RBC was measured at Ln concentrations up to 200 mu M. In another series of experiments, RBC were exposed to mechanical stress (190 Pa, 300 s) at 50 mu M Ln and deformation-stress data obtained prior to and after this stress. Data were fitted to a Lineweaver-Burke model to obtain the shear stress at one-half maximum deformation (SS1/2). Our results include: (1) lanthanides cause decreased cell deformability with the magnitude of the decrease dependent on concentration and shear stress; (2) this decrease of deformability is affected by Ln ionic radius such that La > Nd > Sm > Eu > Dy > Er and is reversible for cells in Ln-free media; (3) mechanical stress decreases deformability (i.e., increases SS1/2) such that compared to control, La and Sm reduce and Dy and Er enhance the mechanical stress effect; (4) the decrease of deformability consequent to mechanical stress scales inversely with Ln ionic radius. These results indicate a reciprocal relation between cell rigidity and sensitivity to mechanical stress that is mediated by Ln ionic radius. Additional studies are clearly warranted, particularly those that explore membrane-glycocalyx and intracellular mechanisms.